2021
DOI: 10.47276/lr.92.4.317
|View full text |Cite
|
Sign up to set email alerts
|

Self-care programmes for people living with leprosy: a scoping review

Abstract: Objective Effective self-care is a key approach for the management and prevention of ulcers for people living with leprosy. Understanding the complexities related to the design and implementation of self-care interventions is key to improving future interventions. The aim of this scoping review is to synthesize the existing evidence on self-care for the prevention and management of ulcers amongst people living with leprosy. Methods We conducted a scoping review using PubMed, Web of Science and Infolep. Studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Self-care can be useful for people with leprosy in wound prevention, a strategy is needed to implement a self-care program and test the use of footwear for people with leprosy. (Ilozumba & Lilford, 2021).In line with the research conducted by Meima et al (2008)revealed that there is a relationship between self-care and the incidence of leprosy defects. This self-care effort can be done alone or together with other sufferers by forming a self-care group (SCG).…”
Section: Introductionmentioning
confidence: 56%
“…Self-care can be useful for people with leprosy in wound prevention, a strategy is needed to implement a self-care program and test the use of footwear for people with leprosy. (Ilozumba & Lilford, 2021).In line with the research conducted by Meima et al (2008)revealed that there is a relationship between self-care and the incidence of leprosy defects. This self-care effort can be done alone or together with other sufferers by forming a self-care group (SCG).…”
Section: Introductionmentioning
confidence: 56%
“…Later on, ulcers on the sole of the feet and even blindness may ensue. 4,5 The good news is that Leprosy is curable and aggressive treatment in the early stage prevents disability. Early diagnosis carries some inherent advantages including the complete cure of the disease before further nerve damage occurs and preventing disabilities, avoiding infecting close contacts, and it also motivates people to seek treatment early.…”
Section: Introductionmentioning
confidence: 99%
“…2 This has also helped patients by decreasing their dependence on the health care givers and encouraging self-management of ulcers. 9 In India and across other leprosy endemic countries, managing plantar ulcers has always been a challenge. The cost involved in healing and managing ulcers could become a burden for the families and for health care providers.…”
Section: Introductionmentioning
confidence: 99%